Gendered dimension of chronic pain patients with low and middle income: A text mining analysis - Peiró, A. M.; Carracedo, P.; Agulló, L.; Bernardes, S. F. (PLoS One, 2024)
Inferences about gender differences and socioeconomic status in Chronic Non-Cancer Pain (CNCP) management may shape health care. This can be a particularly relevant issue for women, who continue to more often assume reproductive gender roles. The objective of this study was to explore the gendered impact of CNCP on low-and middle-income women and men through text mining analysis.